Palliative effects of carnosol on lung‐deposited pollutant particles‐induced thrombogenicity and vascular injury in mice - Sumaya Beegam; Nur Elena Zaaba; Ozaz Elzaki; Abdulrahman Alzaabi; Abdulrahman Alkaabi; Khalifa Alseiari; Nasser Alshamsi; Abderrahim Nemmar (Wiley, 2024)
Abstract The toxicity of inhaled particulate air pollution perseveres even at lower concentrations than those of the existing air quality limit. Therefore, the identification of safe and effective measures against pollutant particles‐induced vascular toxicity is warranted. Carnosol is a bioactive phenolic diterpene found in rosemary herb, with anti‐inflammatory and antioxidant actions. However, its possible protective effect on the thrombotic and vascular injury induced by diesel exhaust particles (DEP) has not been studied before. We assessed here the potential alleviating effect of carnosol (20 mg/kg) administered intraperitoneally 1 h before intratracheal (i.t.) instillation of DEP (20 μg/mouse). Twenty‐four hours after the administration of DEP, various parameters were assessed. Carnosol administration prevented the increase in the plasma concentrations of C‐reactive protein, fibrinogen, and tissue factor induced by DEP exposure. Carnosol inhibited DEP‐induced prothrombotic effects in pial microvessels in vivo and platelet aggregation in vitro. The shortening of activated partial thromboplastin time and prothrombin time induced by DEP was abated by carnosol administration. Carnosol inhibited the increase in pro‐inflammatory cytokines (interleukin‐6 and tumor necrosis factor α) and adhesion molecules (intercellular adhesion molecule‐1, vascular cell adhesion molecule‐1, E‐selectin, and P‐selectin) in aortic tissue. Moreover, it averted the effects of DEP‐induced increase of thiobarbituric acid reactive substances, depletion of antioxidants and DNA damage in the aortic tissue. Likewise, carnosol prevented the decrease in the expression of nuclear factor erythroid 2‐related factor 2 (Nrf2) and heme oxygenase‐1 (HO‐1) caused by DEP. We conclude that carnosol alleviates DEP‐induced thrombogenicity and vascular inflammation, oxidative damage, and DNA injury through Nrf2 and HO‐1 activation.